Proceso de atención de enfermería en mujer de 25 años con diagnóstico de lupus eritematoso sistémico. - González Tapia, David Alejandro (2022)
Systemic lupus erythematosus is a chronic autoimmune disease of unknown etiology and has a wide range of clinical and multisystem manifestations due to the production of autoantibodies against autoantigen and the formation of multiple immune complexes that mediate inflammatory responses by deposits in various organs and tissues. The cause has not been fully elucidated; However, it is known that a variable number of autoantibodies produced, together with genetic and environmental factors. They may be involved with its pathogenesis. Clinical manifestations are highly variable and can range from very mild to severe, which can last a lifetime. Proper and timely treatment improves the patient's quality of life and survival. The most commonly used drugs are glucocorticoids, antimalarials and common immunosuppressants (disease modifiers). He present clinical case based on a 25-year-old female patient in which the nursing care process is applied for a case of systemic lupus erythematosus; the patient upon arrival at the emergency room of the general hospital "Alfredo Noboa Montenegro" on 02/10/2021 presented the following signs and symptoms: pain at the joint level in the upper and lower extremities (arthralgia), fever (hyperthermia), asthenia or decrease in muscle strength and malar erythema shaped like butterfly wings at the facial level of a ruddy pigmentation, after the interview the patient reports being in medical treatment for being diagnosed with systemic lupus erythematosus 6 months ago but 2 weeks ago the patient reports having been in the sun on the beach for more than 4 hours without any sun protection and that she has also been feeling pains, but of less intensity, approximately a week, without taking anything to remedy it. In the development of the clinical case study we used the taxonomies of the NANDA – NIC – NOC, and the nursing theorist Marjory Gordon along with her 13 functional patterns to her evidence we looked for the altered domains and formulated a definitive nursing diagnosis that helps improve the patient's health status as well as her stay within the hospital during the days she stayed in this health house, as the days went by he improved and soon he was able to return to his family but he was given some indications before leaving the hospital letting him know that he can not stop taking his medication prescribed by his rheumatologist, also not be exposed to unprotected sunlight for too long and continue with the treatment but to any suspicion of alteration of the disease again approach the hospital.